DEMOGRAPHIC PREDICTION TOWARDS LEADERSHIP AND TEACHERS’ COMMITMENT AND MOTIVATION IN THE EDUCATIONAL SECTOR - Jabeen, Afshan; Luqman, Muhammad Safdar; Zia-ul-Islam, Syed; Khan, Muhammad Asghar; Manzoor, Mehhwish (Humanities & Social Sciences Reviews, 2021)
Purpose of the study: The existing research study aimed to investigate the predictive effect of demographic traits, leadership styles on teachers’ job commitment and motivation at the college level, in Punjab, Pakistan. Methodology: The population of the study consisted of 576 male and female lecturers (PE). The total number of lecturers (PE) working in all Government colleges is 576, male lecturer (PE) is 366, and female lecturers (PE) are 210. Three self cum closed-ended questionnaires were designed for the data collection. Mean, standard deviation, Independent Samples Test, and One-way ANOVA were applied to test the formulated hypotheses. Main Findings: It was found that there no positive impact of leadership styles of the head of institutions upon professional commitment and motivation of the lecturers based on demographics. It was also found that the study respondents regarding demographic attributes have significant group mean differences in opinion about the research variables under study. Implications of the study: It was recommended that the most motivated and committed worker is the one who is senior, married, educated, and female, has a sound salary package, has served the institution for a long time- period and has a chance of professional development. It was also found that s/he performs his/her duty under an HOI who has more of a transformational leadership style than the rest and should be more transformational. Therefore HOI of the institutions should adopt a transformational leadership style to get maximum output from the employees.